Strategies to Improve Employee Performance: Competency Analysis, Compensation, and Motivation - Hapsari, Betari (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Employee performance is a key element in organizational success. In an effort to understand and improve employee performance, it is necessary to analyze the role played by competence, compensation, and motivation. These factors have long been recognized as key determinants of individual performance. This study aims to identify the relationship between competence, compensation, and motivation with employee performance. This research uses a quantitative approach with data collection through surveys and statistical analysis. A number of employees from different departments and levels in an organization were identified as research samples. Data on their competence, compensation, motivation, and performance were collected through questionnaires. Regression analysis is used to measure the relationship between these variables. The results showed a positive correlation between the level of competence, fair compensation, and high motivation with employee performance. Strong competencies provide a solid foundation for good performance, while adequate compensation and high motivation increase employee productivity and dedication. These findings provide valuable insights for managers and organizational leaders to design effective employee development strategies and appropriate incentive systems.